Crescimento e acúmulo de nutrientes em porta-enxertos de caramboleira adubados com zinco - Lima Neto, Antonio João de [UNESP] (2014)
Brazil is among the world's largest producers of starfruit, with the state of São Paulo accounting for most of the national production. Despite the importance of this culture, information about the fertilization of this culture is scarce in literature, particularly regarding the use of micronutrients in producing rootstocks. Due to lack of information, this study aimed to evaluate the influence zinc has on growth, mineral composition and nutritional efficiency of star fruit rootstocks. The study was conducted between the months of September 2012 and February 2013 in a seedling production nursery located in Taquaritinga, SP. A randomized block design with five doses of zinc was used to carry out the study with four replications and three plants per plot: D0 = zero, D1 = 2, D2 = 4, D3 = 6, and D4 = 8 mg Zn dm-3. At 170 days after applying the zinc, the plant height, stem diameter and number of leaves were analyzed. The plants were then collected and divided into shoots and roots, dried, weighed, ground and the content was evaluated. The accumulations were calculated as well as the efficiency of absorption, transport and utilization of macro and micronutrients. All growth parameters evaluated responded to the zinc doses. The accumulation of Zn, P, K, Mg and S in the plant also responded to the zinc. The higher doses of zinc increased the absorption efficiency of Zn and reduced the transport of Ca and Mn. From these results, it is concluded that largest development of starfruit rootstocks was associated with the dose between 3.1 and 3.8 mg of Zn dm-3. High doses of zinc promote lower content, accumulation and utilization efficiency for most macro and micronutrients